The Relation Between Media Ownership Structure and Public Sphere in Digital Capitalist System: Research on Platform X - SİNAV, Ahmet and EFE, Eren (International Journal of Contemporary Economics and Administrative Sciences, 2025)
New forms of communication created by communication technologies and especially social media necessitate a re-evaluation of the concept of public space within the framework of digitization. By focusing on economic and political power relations within social media, this study argues that new media instruments are subject to the free market-oriented capitalist mode of production and that monopolistic formations are in direct relationship with the ownership structure of networks. As a matter of fact, multinational companies and political decision-makers are dominant actors in the information field produced by new communication technologies in terms of ownership and manageability. The main purpose of the study is to evaluate the debate on whether social media can create a democratic public sphere through Elon Musk’s acquisition of Twitter and rebrand it under the name X. In this regard, Elon Musk’s effort to shape online discourses on platform X during US Presidential Elections in 2024 was interpreted by analyzing 407 posts between October 30 - November 5. According to the results, the idea that social media creates a democratic public space ignores the potential of these areas to reproduce power relations in the capitalist social structure. As a result of applications such as algorithm-based automation processes and target audience analysis, the digital public space has been put into a frame with certain concepts like "echo chamber" and "filter bubble". For this reason, social media platforms are moving away from one of the essential requirements of public sphere, namely the function of bringing different ideas together. In light of Twitter, Musk’s acquisition of it has undermined the public sphere discourse that was put forward in reference to social media platforms.